Key Factors to Consider in Team Meetings when Dealing with Multimorbidity in Primary Care: Results from a Delphi Panel - Prazeres, José Filipe Chaves Pereira (2019)
Background: Multimorbidity brings several difficulties and challenges to the daily work of primary care teams. Team meetings are opportunities to discuss approaches and solutions on how to best manage multimorbid patients. Objective: This qualitative study aimed to collect a consensus, from general practitioners that deal with multimorbid patients, about their perspectives regarding multimorbidity team meetings in primary care. Methods: The study followed a modified Delphi method with 15 Portuguese general practitioners. After every round of responses, results were analyzed, and justifications for non-consensual items were aggregated by the investigators, and then a new Delphi round with the revised questionnaire was again initiated. This process was repeated until consensus has been reached. Results: Overall, a list of 10 key themes associated with the ideal meeting was agreed: (a) definition; (b) setting; (c) duration; (d) frequency; (e) number of participants; (f) attendance; (g) requirement of patient’s presence; (h) number of patients/clinical cases; (i) structure of the meeting; and (j) sharing meeting results. The consensus was achieved after two Delphi rounds with a mean score between 7.9 and 8.7 (maximum score of 9.0 per key theme). Conclusion: The complexity of multimorbidity affects meetings’ periodicity, duration, and participants. Ideally, it should be an interprofessional primary care team meeting. Further research exploring meeting outcomes (organizational effectiveness and healthcare quality) of the proposed factors is needed before they can be recommended for general use.